Penggunaan Silt Screen untuk Proteksi Alur Pelayaran terhadap Siltasi - Alfalah Alfalah (KEAIRAN, 2005)
Indonesian beaches commonly took mud as basic material which are washed away by river flow from mainland during flood period. Navigational channels built in muddy beaches surely suffer from siltation resulted from wave and current transported fluid mud.Siltation in navigational channels mostly formed by fluid mud sedimentation and with a little contibution from accumulated suspended sediment. Common strives taken after are to build fix structure such as breakwater and submerge dike.The research will examine movable structure (silt screen) to decrease siltation rate in navigational channels.In the process, the research will use 2 dimentional mathematical model as well as physical one. The expected results would be optimal silt screen form and the value of siltation reduction rate in the navigational channels comparing with those without silt screen.Keywords: Silt screen, fluid mud sedimentationPermalink: http://ejournal.undip.ac.id/index.php/keairan/article/view/2736[How to cite: Alfalah (2005). Penggunaan Silt Screen untuk Proteksi Alur Pelayaran terhadap Siltasi, Jurnal Keairan, 12 (2): 43-53]